2015
DOI: 10.1007/978-3-662-48008-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Reviews on Impact Assessments of Land-Use Change on Key Ecosystem Services

Abstract: It is commonly acknowledged that land-use change (LUC) and climate change have exerted significant effects on ecosystem services which are essential and vital to human well-being. This chapter conducted a revisit to relevant researches on the impacts of LUC on human well-being via specifically altering the ecosystem provisioning services and climate regulation services. As to the issues related to ecosystem provisioning services, first, the explorations on the influences of LUC on ecosystem provisioning servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 107 publications
(109 reference statements)
1
5
0
Order By: Relevance
“…In contrast, approximately two-thirds of the total water yield was produced by grasslands and forest ecosystems. Referring to some previous studies [ 24 , 47 ], the results of our study also showed that abundant shrub or grass planting in the catchment can increase water yield and have positive quantified effects on the hydrological cycle. Besides these habitat types, the tropical rain forest also enhances the landscape resilience to hydrological change, and plays a significant role in water conservation [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, approximately two-thirds of the total water yield was produced by grasslands and forest ecosystems. Referring to some previous studies [ 24 , 47 ], the results of our study also showed that abundant shrub or grass planting in the catchment can increase water yield and have positive quantified effects on the hydrological cycle. Besides these habitat types, the tropical rain forest also enhances the landscape resilience to hydrological change, and plays a significant role in water conservation [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 85%
“…The composition and configuration of different ecosystems within a changing landscape are so influential to the alteration of biochemical and biophysical conditions, that the provision of ecosystem service from these conservation hotspots may be affected [ 24 , 25 ]. In this unique tropical region in China, conservation priorities are rarely related to the management of ecosystem services [ 26 ], and the interaction between landscape patterns and ecosystem services is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have satisfied the need to obtain resources for their survival, such as water, wood, food, and fibre, by transforming natural ecosystems [1,2]. Approximately half of the Earth has been directly transformed by human activities [3][4][5][6].…”
Section: Introduction 1land Use and Land Cover Contextmentioning
confidence: 99%
“…There is a clear relationship between anthropogenic activities, climate change, and their impact on ecosystems [2,55,56]. Climate change is an essential driver of the distribution of biomes on Earth, and several predictions indicate that in the future, climate change could alter the environmental conditions of different ecosystems in response to human activities [26].…”
Section: Introduction 1land Use and Land Cover Contextmentioning
confidence: 99%
See 1 more Smart Citation